2023
DOI: 10.3390/foods12061213
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Two-Step Sous Vide Cooking and Storage on Microbiological and Oxidative Stability of Chicken Breast

Abstract: A two-step sous vide method, which included a low temperature initial stage, was shown to improve texture parameters, increase the solubility of proteins, and decrease the cook loss in chicken breasts. The current work was designed to determine the effect of two-step sous vide and subsequent storage on the microbiological and oxidative stability of chicken breasts. Inoculated chicken breasts were vacuum packaged and cooked at two temperatures, 50 °C and 60 °C, combined in different ratios of the same total coo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…All treatments added with EIP showed lower PV values but higher TBARS values than those of PC and NC (p<0.05). Han et al (2023) reported that the TBARS value of hybrid sausage added with cricket flour increased. Also, it has been reported that adding silkworm pupae flours to emulsion sausage increases the TBARS value (Kim et al, 2016).…”
Section: Tmc Lipid Oxidation (Tbars Pv)mentioning
confidence: 99%
“…All treatments added with EIP showed lower PV values but higher TBARS values than those of PC and NC (p<0.05). Han et al (2023) reported that the TBARS value of hybrid sausage added with cricket flour increased. Also, it has been reported that adding silkworm pupae flours to emulsion sausage increases the TBARS value (Kim et al, 2016).…”
Section: Tmc Lipid Oxidation (Tbars Pv)mentioning
confidence: 99%
“…This stands in contrast to the stewing method, which involves slowly heating the meat in the broth to liberate the fatty acids and amino acids and produce the desired flavors or volatiles (Guan et al, 2023). Boiled and pasteurized chicken meat has a shelf life of up to 7 d under mild chilling conditions with acceptability of flavor and odor (Montero-Prado and Morales, 2022) and customer safety (Hasani et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Today, it is not only used alone but also in combination with other lowimpact processes, as these combined processes can reduce the food safety risk associated with the technology due to the low-temperature heat treatment. Forward-looking results have been obtained for sous-vide chicken breasts, where the temperature was increased in several steps during the heat treatment [10][11][12]. Both the texture, weight loss values, and organoleptic properties were improved compared to the single-step treatment.…”
Section: Introductionmentioning
confidence: 99%